Athena: the X-ray observatory to study the hot and energetic Universe. (April 2015) - Barcons, X; Nandra, K; Barret, D; den Herder, J-W; Fabian, A C; Piro, L; Watson, M G
Abstract: Hot gas pervades the Universe: about half of the baryonic content in the Universe is expected to be at T > 10 5 K, and there are as many baryons at T > 10 7 trapped in galaxy clusters as there are locked into stars. There is an intimate relation between this hot gas, which delineates the large-scale structure of the Universe, and the most energetic phenomena occurring in the immediate vicinity of super-massive black holes, through a poorly known process called Cosmic Feedback. Studying the hot and energetic universe requires X-ray observatories in space, whose capabilities greatly exceed those of the current workhorse observatories: NASA's Chandra and ESA's XMM- Newton. Athena has been selected by ESA as the L2 mission (due for launch in 2028), to address the "Hot and Energetic Universe" science theme. It will be a large X-ray observatory capable of addressing the above topics, and many other fundamental questions in contemporary astrophysics. Here we present the Athena science objectives, the mission concept and its payload, including the X-ray telescope and its two baseline instruments: a Wide Field Imager (WFI) and an X-ray Integral Field Unit (X-IFU).